Adsorption of hexoses on the Ti2CO2 MXene - Gouveia, J. D. (2024)
In this study, we employed density functional theory calculations to investigate the adsorption behavior of α and β isomers of d-glucopyranose, d-galactopyranose, d-fructopyranose, and d-mannopyranose on the Ti2CO2 MXene surface, in order to understand the potential of this material for sensing sugars. The adsorption process was found to occur via strong noncovalent interactions, primarily through hydrogen bonding and with the hexoses oriented parallel to the surface. The calculated adsorption energies vary between −0.78 (α-d-fructopyranose) and −1.00 eV (β-d-glucopyranose). Importantly, while the charge transfer was found to be negligible, the work function of the material was found to change by up to 0.3 eV in the case of the compound that adsorbs most strongly, β-d-glucopyranose, while less important changes were found for the other studied hexoses. We also explored the influence of defects in the MXene structure on the adsorption of β-d-glucopyranose and observed that oxygen or titanium vacancies enhance the adsorption strength. These findings indicate that the Ti2CO2 MXene is a promising candidate for selective glucopyranose sensing, which can be interesting for glucose detection applications.